Rumah Fiqih Indonesia : Challenging The Fatwa Shopping - Muhammad Irfan Wahid (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2020)
Most of the websites that offering online fatwa favour a question and answer format, wherein guidance is provided by a particular imam, or sometimes by a team of religious scholars. Recently, Muslim often choose to ask their questions online for a number of reasons. The internet is among the most important media today to navigate Islamic value in daily life. The internet gives people in urban areas an extra tool to quickly access the information they need with much quicker and easier way of obtaining answers. The merit of online fatwa is that they allow almost anyone to set themselves up as an authority and issue legal opinios that can leads to information anarchy. It becomes even more difficult to know what information is credible and what is not. In absence of a formal framework for deciding who can become an internet mufti, it is very hard to stop people from declaring themselves to be Muslim scholars. In Indonesia, several Muslim scholars built a study center which they named the Indonesian Fiqh House (Rumah Fiqih Indonesia). The study center also often presents online fatwa and discusses several Islamic thought issues. To find out how Rumah Fiqih Indonesia present online fatwa content and the extent of their credibility with Islamic literature, this paper uses a content analysis approach. The result, it was found that Rumah Fiqih Indonesia continued to use traditional and conventional approaches by providing answers using reliable reference sources even though using the internet as a media for their publication.